Deep Shave Removal of Suspected Basal Cell Carcinoma: A Prospective Study. Issue 2 (26th February 2023) - Dando, Emily E.; Abban, Cynthia; Shehu Wingrove, Aurora; Pugliano-Mauro, Melissa; Ferris, Laura; Ho, Jonhan; Patton, Timothy
Abstract : BACKGROUND: Diagnosis and treatment of basal cell carcinoma (BCC) in the same visit by shave removal may decrease health care spending and promote patient satisfaction. OBJECTIVE: To prospectively evaluate deep shave removal of lesions clinically suspicious for low-risk BCC on the trunk or extremities in immunocompetent patients. MATERIALS AND METHODS: Deep shave removal with the intent to remove the entire tumor was performed from January 2015 to June 2016, and patients were followed prospectively for clinical evidence of tumor recurrence. RESULTS: Seventy-seven lesions were removed from 51 patients, including 29 (37%) superficial and nodular BCCs, 27 (35%) superficial BCCs, 16 (21%) nodular BCCs, and 5 (6%) non-BCCs. Fifteen BCCs (21%) had positive residual margins after deep shave removal, which was significantly more likely to occur in nodular compared with superficial BCCs (odds ratio = 7.8, 95% confidence interval = 1.4–43), and underwent re-excision. Fourteen specimens initially reported to have negative margins after deep shave underwent resectioning, which revealed positive margins in 4 specimens (28.6%). No BCCs have recurred clinically after an average follow-up of 50 months (SE 3.2). CONCLUSION: Consider deep shave removal for low-risk BCCs on the trunk or extremities in immunocompetent patients hoping to avoid a second treatment visit.